Jump height ingenerated by countermovement and arm swing better correlates with proagility shuttle run tests but not with change of direction deficits in collegiate female athletes - Yamashita, N.; Sato, D.; Mishima, T. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Jumping and linear sprinting performances show a moderate correlation with change of direction (COD) ability. However, the extent of these correlations remains unknown through statistical analysis. Thus, this study statistically compared correlation coefficients between COD, COD deficit (CODD), and jumping and linear sprint performances. METHODS: National-level basketball (29) and baseball (18) intercollegiate female athletes performed 20-m linear sprint, proagility (5-10-5) test, squat jump (SJ), countermovement jump with (CMJarm) and without (CMJ) arm swing and modified reactive strength index (RSImod). Correlation analysis was used to assess factors correlated with COD performance and CODD; subsequently, correlation coefficient comparison test was used to determine better correlations with COD and CODD performance. RESULTS: CMJ (r=-0.483) and CMJarm (r=-0.446) had stronger correlations with 10-m COD (both, P<0.018) than with 10-m linear sprint (r=0.431, P=0.002). For 20-m COD, RSImod, CMJ, and CMJarm (r=-0.491--0.543, P<0.001) better correlated with 20-m COD than with 20-m linear sprints (r=0.436, P=0.002), while RSI (both r=-0.317, P<0.030) and SJ (r=-0.359, r=-0.293, P=0.046) were weakly correlated with 10- and 20-m COD. The differences in correlation coefficients for RSImod, CMJ, and CMJarm were not significant in both 10- and 20-m COD. Ten-meter linear sprint performance only correlated with 10-m CODD, while no correlation was observed with 20-m CODD. CONCLUSIONS: Stronger correlations of RSImod, CMJ, and CMJarm with 10-/20-m COD than with linear sprinting, RSI, and SJ suggest that training focused on improving countermovement and arm swings with jumping may enhance COD performance in female athletes.